Christology of the Old Testament ; v. 2 and a commentary on the Messianic predictions - Hengstenberg, Ernst Wilhelm, 1802-1869 (Edinburgh, Scotland T. and T. Calrk, 1858)
Contents : v. 2 : Messianic predictions in the prophets : The prophet Isaiah - The prophet Zephaniah - The prophet Jeremiah.
Keywords: Christology; Bible. O.T. -- Messianic prophecies